2017
DOI: 10.3758/s13423-017-1390-9
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric asymmetry of liking for representational and abstract paintings

Abstract: Although the neural correlates of the appreciation of aesthetic qualities have been the target of much research in the past decade, few experiments have explored the hemispheric asymmetries in underlying processes. In this study, we used a divided visual field paradigm to test for hemispheric asymmetries in men and women's preference for abstract and representational artworks. Both male and female participants liked representational paintings more when presented in the right visual field, whereas preference fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…We also asked participants to either pay attention to the images or to evaluate them aesthetically, so to force in the latter case an aesthetic orientation that may drive specific brain activations. If, as suggested by prior studies using the divided visual field paradigm (Coney & Bruce, 2004;Nadal et al, 2018), the left hemisphere is more involved than the right in aesthetic appreciation of figurative paintings, we should observe a reduction in the leftward attentional bias with paintings (but also possibly with photographs, if these also trigger in the observer a local analysis of the content). In turn, if right hemispheric resources involved in visuospatial processing on the one hand (Cupchik et al, 2009;Di Dio et al, 2016;Fairhall & Ishai, 2008) and in reward processing on the other (Di Dio et al, 2007Dio et al, , 2011Lacey et al, 2011;Vartanian & Goel, 2004) play a major role in aesthetic viewing, then the expected leftward bias may even increase when lines appear on paintings (and on non-artistic photographs, at least when an explicit aesthetic evaluation is required for the latter).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…We also asked participants to either pay attention to the images or to evaluate them aesthetically, so to force in the latter case an aesthetic orientation that may drive specific brain activations. If, as suggested by prior studies using the divided visual field paradigm (Coney & Bruce, 2004;Nadal et al, 2018), the left hemisphere is more involved than the right in aesthetic appreciation of figurative paintings, we should observe a reduction in the leftward attentional bias with paintings (but also possibly with photographs, if these also trigger in the observer a local analysis of the content). In turn, if right hemispheric resources involved in visuospatial processing on the one hand (Cupchik et al, 2009;Di Dio et al, 2016;Fairhall & Ishai, 2008) and in reward processing on the other (Di Dio et al, 2007Dio et al, , 2011Lacey et al, 2011;Vartanian & Goel, 2004) play a major role in aesthetic viewing, then the expected leftward bias may even increase when lines appear on paintings (and on non-artistic photographs, at least when an explicit aesthetic evaluation is required for the latter).…”
Section: Introductionmentioning
confidence: 73%
“…Whether art-viewing engages the two hemispheres to a different extent is still a matter of debate, with different processes involved in aesthetic evaluation being possibly differently lateralized in the brain. A predominant local (vs. global) analysis of the content may be responsible for the higher recruitment of the left hemisphere during preference decisions for figurative paintings, as suggested by prior studies using a divided visual field paradigm (Nadal et al, 2018; see also Coney & Bruce, 2004), with local processing mainly involving the left hemisphere (Han et al, 2002;Yovel et al, 2001). Directing attention to aesthetic orientation seems to also specifically activate the left hemisphere, and in particular, the prefrontal cortex (Cela-Conde et al, 2004;Cupchik et al, 2009), a finding though that may also depend on righthandedness of participants (see Cela-Conde et al, 2004).…”
Section: Introductionmentioning
confidence: 87%
“…In addition, their appraisal of a piece of art is guided mainly by semantic features (Parsons, 1987;Schmidt et al, 1989). Hence, our participants might have discovered nothing but meaningless brushstrokes when appreciating an abstract painting (Nadal et al, 2018) regardless of the complexity, which presumably led them to be satiated only after a few repeated views and to create bias in their preference toward a novel painting (Berlyne, 1970;Montoya et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
“…To discuss this result, it should be noted that the participants of the current study had no formal training in art or a degree in any art-related major. Previous studies have shown that viewers with limited experience in art tend to focus more on recognizable objects rather than on background and relations among elements (Nodine et al, 1993;Zangemeister et al, 1995;Vogt, 1999;Vogt and Magnussen, 2007;Cattaneo et al, 2015;Nadal et al, 2018). They also rely primarily on cognitive processes such as identifying depicted objects and understanding scenes (Cupchik, 1992;Winston and Cupchik, 1992;Nodine et al, 1993;Cela-Conde et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Linear mixed effects models are, thus, well suited to analyze preference responses, given that these often vary from one person to another and also from one object to another (Silvia, 2007). For this reason, they have been used successfully in experimental aesthetics (Brieber et al, 2014; Cattaneo et al, 2015; Mühlenbeck et al, 2015; Nadal et al, 2018; Vartanian et al, 2019). They are especially well suited to the purposes of the current study, because they provide estimates for group‐level effects, which can be compared with previous studies, and estimates for participant‐level effects, which constitute our measure of individual aesthetic sensitivity.…”
Section: Analysesmentioning
confidence: 99%